Penerapan Konseling Individu Dengan Teknik Roleplay Untuk Mengatasi Kecanduan Gadget Pada Anak Usia Dini ( Studi Kasus Klien X Di Kecamatan Sembawa ) - Dewi Anggraini; Abdur Razzaq; Lena Marianti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is entitled "Application of Individual Counseling Using Roleplay Techniques to Overcome Gadget Addiction in Early Childhood (Case Study of Client "X" in Sembawa District)" Gadget Addiction is an attachment to gadgets which is accompanied by a lack of control and has negative impacts. Because client "X" has been used to playing with gadgets since he was 2 years old, so it is difficult for him to get away from his gadgets. This research was conducted with the aim of finding out the description of Gadget Addiction experienced by client "X" and also wanting to know the process of implementing individual counseling using roleplay techniques in overcoming gadget addiction in client "X" in Sembawa District. This research uses a qualitative approach with case study research methods. The subject in this research is client "X". The data collection techniques used are observation, interviews and documentation. Meanwhile, the data analysis techniques used are data reduction, data transfer, and drawing conclusions. The results of the research show that the description of gadget addiction experienced by client "X" contains several aspects, including the aspect of not being able to control use, the Anxiety aspect, the Feeling lost aspect, the withdrawal and escape aspect, the Productivity loss aspect. In the application of individual counseling using roleplay techniques, six meetings were held with three stages, namely the initial stage, the middle stage or work stage, and the final stage. Overcoming gadget addiction using the roleplay technique is a role playing process by playing several games at each counseling meeting, namely playing while learning, drawing and coloring a mask of an animal and then the client acting out the animal, playing the role of traders and buyers, coloring a picture of the client's ideal profession. “x” (police officer) then client “X” plays the role of an architect, reads a story book.